Losing Political Representation - Aaron Günther; Niklas Potrafke; Felix Rösel; Timo Wochner (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
What are the consequences of losing political representation in a democracy? A reform of Germany's mixed electoral system left more than 7 million citizens in 23 constituencies without a directly elected representative after the 2025 national election. Which and how many constituencies were affected was unpredictable and quasi-random. We show that losing political representation reduces citizens' satisfaction with democracy. Moreover, discontent is independent of party preferences and spreads through social networks, reducing democratic satisfaction even among individuals who were unaware of the reform's outcome. Political representation is a cornerstone of democracy; its erosion may give rise to democratic backsliding.
Keywords: D02; D72; P11; 330; political representation; democracy; social networks